(untitled) (Conference on English Language Teaching, 2023)
This study utilized a classroom action research design to examine the efficacy of a genre-based approach in improving the writing skills of vocational school students. Thirty-four secondary school students in a Kutai Kartanegara East Kalimantan vocational school were instructed to use a genre-based approach for twelve weeks in this investigation. The strategy included teaching students exploratory and exploratory writing and providing feedback and opportunities for revision. Data collected through classroom observations, student work samples, and interviews supported the findings. The research discovered that genre-based instruction improved students’ writing abilities. The student’s abilities to write exploratory and procedural texts, employ appropriate language features and structures, and organize their thoughts were enhanced. In addition, the student’s writing motivation and engagement increased. This study suggests a genre-based instructional strategy can improve students’ writing abilities. Students can develop their writing skills systemically and systematically, preparing them for various writing duties and assessments. The study has significant implications for secondary school instructors and curriculum designers who wish to improve students’ writing abilities. Additionally, it highlights the significance of classroom action research.